ANALISIS LAYANAN PUSKESMAS TERHADAP KEPUASAN PASIEN PEMEGANG KARTU ASURANSI KESEHATAN KELUARGA MISKIN DI KOTA BOGOR - yuningsih, erni (Universitas Djuanda Bogor, 2010)
The biggest challenge in providing health service is the fulfillment of people, especially the poor, expectation in getting appropriate health service quality and facility. Puskesmas (public health center) is the front liner in providing public health service and in national health system. Therefore, the government role in improving the access of poor people to health service through health maintenance guarantee program for poor people. An analysis of the effects of Puskesmas service quality on the satisfaction of poor family health insurance holder patients in Bogor city seen from tangibility, empathy, reliability, responsiveness, and assurance dimensions was done. Results showed that puskesmas service still needed improvement especially in facility completeness and medicine supply. Simultaneously, service quality parameters were found to give significant effects. Partially, it was found that tangibility, responsiveness, and assurance gave significant effects but empathy and reliability did not.